Dematiaceous Hyphomycetes from North Maharashtra - Patil, S Y; Borse, B D (International Multidisciplinary Research Journal, 2012)
The present paper deals with three species of Dictyosporium Corda viz. Dictyosporium elegans Corda, Dictyosporium cocophilum Bat and Dictyosporium tetraseriale Goh,Yanna and Hyde were collected from the submerged wood samples from the various water bodies in North Maharashtra region. Two species viz. Dictyosporium cocophilum Bat and Dictyosporium tetraseriale Goh,Yanna and Hyde are recorded for the first time form India. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.